FMEA quality method: a study of its application to the embroidery process in a regional company - Gabriel Silva Santos, Johnny; Fernandes Rodrigues, Enio (Latin American Journal of Energy Research, 2024)
With the increase in competitiveness in the market and the rigorous way in which companies have analyzed their processes in order to make them more efficient and assertive, quality management has become an important area of study for managers and organizations to find methodologies and techniques that can elucidate their process and reduce recurring and possible failures in their production system. In this context, FMEA is an important auxiliary tool for mapping faults and errors in a process, revealing its adversities and proposing solutions to improve the company’s efficiency and assertiveness. With this, FMEA is based on one of the principles of quality management: full customer satisfaction, with a view to reducing costs. Therefore, the aim of this study was to analyse the embroidery process of a regional company in São Paulo, taking into account the use of FMEA as a tool for identifying and characterizing faults and errors in the process, in order to establish corrective actions to improve production. Therefore, despite the fact that the company does not use any quality control measures, the relevance that FMEA can bring to the organization is determined from the tabulation of problems in its processes and the development of objectively implementable solutions, reinforcing the effectiveness and adaptability of this tool.